Experimental Study on the Atomization and Chemiluminescence Characteristics of Ethanol Flame - Qing Zhang; Xudong Song; Qinghua Guo; Yan Gong; Chonghe Hu; Guangsuo Yu (Journal of Spectroscopy)
The breakup regime in ethanol diffusion flame under different conditions was studied by the high speed camera system combined with the UV camera system. Spray angle and Weber number (We) were used to represent the change of breakup regime. With the increases of spray angle and We, the breakup mode changes from the Rayleigh-type breakup regime to the superpulsating regime. The reaction area and intensity of ethanol flames under different breakup regimes could be discussed by the OH⁎ distribution. From Rayleigh-type breakup regime to superpulsating breakup regime, the OH⁎ distribution increased and the oxidation-reduction reaction area expanded. At the condition of superpulsating breakup mode, the intensity of OH⁎ was significantly higher than that of other modes. The flame luminous length can be obtained by the OH⁎ emission, and OH⁎ distribution reflects the structure of flame. When the breakup regime changes from the fiber-type breakup regime to the superpulsating regime, the flame luminous length increases suddenly.